(untitled) (Contemporary Journal of Social Science Review, 2025)
The integration of artificial intelligence (AI) has transformed digital marketing and product success, providing businesses with tools to personalize consumer experiences. This study explores the impact of AI integration on digital marketing effectiveness and product success among online shoppers, aiming to understand AI’s role in enhancing consumer engagement and product performance. A positivist paradigm guided the quantitative, cross-sectional methodology, using self-administered questionnaires to collect data from consumers who shop online. Convenience sampling yielded a sample size of 214 respondents, with data analyzed using SPSS for descriptive and reliability statistics and AMOS for confirmatory factor analysis (CFA) and structural equation modeling (SEM). Results indicate a significant positive impact of AI integration on both digital marketing and product success, with digital marketing mediating the relationship between AI and product outcomes. These findings underscore the strategic value of AI-driven personalization and data analytics in optimizing marketing and product strategies, allowing businesses to better meet customer needs. Limitations include the cross-sectional design and reliance on self-reported data, which may introduce bias. Future research should adopt longitudinal designs, examine diverse demographics, and explore emerging AI technologies like predictive analytics and augmented reality to deepen understanding of AI’s evolving role in digital marketing. This study highlights AI’s critical role in achieving competitive advantage in the digital economy.